The mathematical model and numerical calculation method of efflorescence. (1st March 2018) - Qian, Chunxiang; Wang, Jian; Cao, Tianji; Qu, Jun; Guo, Jingqiang
Abstract : Efflorescence is a common phenomenon of cement‐based materials, and the mathematical model can be used to simulate the process of efflorescence process calcium dissolution. It is inspired by the dissolution of cement‐based materials, and the Gerard model of calcium leaching is also used for reference. The mathematical model of efflorescence of cement‐based materials is established which based on the calcium ion solubility. It reveals the mathematical relationship of transformation process of Ca(OH)2 between solid phase and liquid phase and the calcium ion transport process in liquid phase. Also, the relationship between Ca(OH)2 content, the porosity, raw materials with physical and chemical properties of cement‐based materials and the key parameters on the mathematical efflorescence model are studied. The related physical and chemical parameters of cement‐based materials are taken into the mathematical model, and the liquid calcium ion distribution inside the material can be calculated after some time of efflorescence, which provides the basics of mathematical model for the prediction of efflorescence.